Hypertension and Drug Adherence in the Elderly - Burnier, Michel; Polychronopoulou, Erietta; Wuerzner, Gregoire (Frontiers in Cardiovascular Medicine, 2020)
Hypertension is highly prevalent after the age of 65 years affecting more than 60% of individuals in developed countries. Today, there is sufficient evidence from clinical trials that treating elderly subjects with hypertension with antihypertensive medications has a positive benefit/risk ratio even in very elderly patients (>80 years). In recent years, partial or total non-adherence has been recognized as major issues in the long-term management of hypertension in all age categories. However, whether non-adherence is more frequent in hypertensive patients older than 65 years or not is still a matter of debate and the common belief is that adherence is lower in older than in younger patients. Are clinical data supporting this belief? In this brief review, we discuss the topic of drug adherence in elderly in the context of the medical treatment of hypertension. Studies show that drug adherence is actually better in patients aged 65 to 80 years when compared to younger hypertensive patients (<50 years). However, in very old patients (>80 years) the prevalence of non-adherence does increase. In this patients’ group, there are specific risk factors for non-adherence such as cognitive ability, depression and health believes, in addition to classical risk factors for non-adherence. One important aspect in the elderly is the prescription of potentially inappropriate medications that will interfere with the adherence to necessary treatments. In this context, an interesting new concept was developed few years ago, i.e. the process of deprescribing. Thus, today, in addition to conventional guidelines recommendations (use of single pill combinations, individualization of treatments), the evaluation of cognitive abilities, the regular assessment of potentially inappropriate medications and the process of deprescribing appear to be three new additional steps to improve drug adherence in the elderly and thereby ameliorate the global management of hypertension.